Examining the Content Validity of Android-Based Augmented Reality Media for Chemical Bonding using Rasch Model - Sri Yamtinah; Sri Retno Dwi Ariani; Martha Andriyanti; Sulistyo Saputro; Endang Susilowati; Ari Syahidul Shidiq; Dimas Gilang Ramadhani; Isma Aziz Fakhrudin (Postgraduate, University of Mataram, 2021)
21st-century learning presents chemistry teachers with new challenges in teaching abstract chemistry concepts with various technologies that continue to develop. One of the media that can visualize abstract chemical concepts is Augmented Reality (AR). AR media developed in chemistry learning needs to be valid so that it can be used properly. Therefore, this study aims to examine the validity of the Android-based AR media developed. Four education practitioners carried out the validation as experts, and 13 students participated as respondents. The instrument used is a questionnaire with a Likert scale. The data obtained were analyzed quantitatively with the Rasch model using the facet software. The results of the analysis show that the Exact Agreements are 41.10%, and the Expected Agreements are 42.20%. The most challenging aspect to achieve is media design, while profit is the most easily agreed-upon aspect. Based on this assessment, in the development of augmented reality media, it is necessary to pay attention to display aspects and 3D objects suitable for viewing a material so that it is easier for users to understand the material.